With tutor’s eyes: a look at the virtual programs developed by SENA - Cadena Cruz, Tatiana Paola
The National Service of Learning (SENA) is a public entity of the national order created in 1957 and attached to the Ministry of Labor. During its 60 years of history, the SENA has been at the forefront of pedagogical and methodological strategies for technical and technological education; as an innovative and constantly evolving entity decided to enter into virtual training. Since 2003, it has been offering virtual programs, whose design has gradually changed over time, to a higher level of development at present. Every year increases the number of people interested in enrolling in these programs. However, high drop-out rates, as well as the absence of rigorous analysis, monitoring and evaluation in the instructional design process, reveals a problem that needs to be reviewed to improve this type of training. This article seeks to give a first glance, from the author’s own experience like tutor, to the courses in learning virtual environments offered by the SENA.